BUILDING INFORMATION MODELLING – BIM – DISSEMINATION STRATEGY FROM THE IMPLEMENTATION OF REGIONAL ENGINEERING AND ARCHITECTURE OFFICES IN UNIVERSITIES AS AN INNOVATION AND GOVERNANCE POLICY - Aglailton de Oliveira Magalhaes; Regina Negri Pagani (Encontro Internacional de Gestão, Desenvolvimento e Inovação (EIGEDIN), 2024)
Seeking to meet purposes of disseminating Building Information Modelling (BIM) in the Brazilian States, the government of the State of Paraná – Brazil –, aiming at the Evolution of processes in the AEC Industry (Architecture, Engineering and Construction), implemented Regional Engineering and Architecture Offices – Projetek – in the state universities serving city halls with up to thirty (30) thousand inhabitants. While universities are fully updating this curriculum and replacing 2D technology in their laboratories. The methodological approach adopted was based on the analysis of the perspectives of a multidisciplinary team characterized by the diversity of training and levels of proficiency in BIM. Additionally, data from projects prepared by the team were collected and examined, providing additional insights into the practical application of BIM. The exploratory approach of this research stands out due to the recent creation of Projetek. The results were satisfactory with regard to the success of implementation, the Evolution of learning, the adaptation to the New Bidding law and the projects delivered whose interoperability and compatibility of disciplines avoided conflicts and, consequently, rework, as well as the preparation of more efficient budgets lean and with the prospect of avoiding additional time and public funds.